Association between unhealthy behavior and sleep quality and duration in adolescents - Luana Peter Hoefelmann; Kelly Samara da Silva; Adair da Silva Lopes; Luciana Gatto de Azevedo Cabral; Cecília Bertuol; Alexsandra da Silva Bandeira; Markus Vinicius Nahas (Universidade Federal de Santa Catarina, 2015)
Inadequate sleep has been associated with unhealthy behavior in adolescence. This study aimed to estimate the prevalence of negative sleep indicators (perceived poorquality sleep and insufficient sleep duration) among students and to identify unhealthy behaviors associated with this outcome. This study is part of a school-based, cross-sectional survey conducted in 2011 in adolescents from Santa Catarina State, Brazil. High school students aged 15 to 19 years (n = 6,529) and enrolled in state public schools participated in the study. The students responded to a questionnaire on the number of hours slept (insufficient: < 8 h, sufficient: ≥ 8 h); perceived sleep quality (good or poor); and behavioral variables. Multinomial logistic regression was performed using reports of positive sleep indicators, and negative reports of one or two sleep indicators. Approximately 30% of adolescents reported a negative perception of sleep, indicating poor quality and insufficient duration. The use of computers/videogames (≥ 4 h/d) and excessive consumption of alcoholic beverages, salty snacks or sweets were associated with negative sleep indicators. A high number of young people displayed one or two negative sleep indicators, and it was found an association between these indicators and a number of unhealthy behaviors.